INTERAKSI ANTARA KYAI DAN SANTRI DALAM MEMBENTUK KEMANDIRIAN ANAK PADA PONDOK PESANTREN ANAK-ANAK - Subekti, Yusuf Agung; Mutamakin, Mutamakin (TA'LIMUNA: Jurnal Pendidikan Islam, 2017)
Independent attitude education for santri (student in islamic boarding school) has existed in Indonesia since long time ago, in general, the pesantren (Islamic boarding school) specializing handle prioritize education of children to read and write the Koran, which is the core element kiai, Mrs. housekeeper, teacher council, students, mosque, hostel, and learning curriculum Koran has become a sub-culture of its own. Because of the character education very early age how urgent it is to form a sub-culture of personal private life tough face reality era of modernization and globalization. In addition, many stakeholders stated that schools are educational institutions that can serve as a model character education in Indonesia. Two questions will be addressed in this paper is how interaction between kyai and santri in forming children's independent attitude Â on kids boarding shool This study focuses attention on Nur Mamba'ul Hisan Satreyan Kanigoro Blitar.